The Influence Of CEO Turnover And Committee Audit Characteristic Toward Audit Fees - Shabrina Herawati; Yustrida Bernawati (Jurnal Akuntansi, 2020)
This study aims to test empirically the effect of CEO turnover and the frequency of audit committee meetings on external audit fees. The population of this research is all manufacturing companies listed on the IDX in 2018-2019. By using the purposive sampling technique, obtained a sample of 103 companies in 2 years. This study uses secondary data in the form of annual reports where data is obtained from the IDX or the Company's website. Hypothesis testing uses quantitative methods with multiple regression analysis techniques. To test the impact to make it more credible, control variables are used, namely Return On Assets (ROA) and Total Assets. The results of hypothesis testing show that CEO turnover and audit committee meeting frequency do not affect audit fees. Meanwhile, ROA and total assets have a significant positive effect on external audit fees.